O ensino de literatura na perspectiva do Pibid: relato de uma experiência. - Barbosa, Samaritana de Moura (Universidade Federal do Tocantins, 2022)
This course conclusion work aims to report experiences as a participant Scholar PIBID, a project that aims the linking between teaching and learning. It is a case study in a School Unit in the city of Araguaína-TO. The research was developed in the Letters course project that was built to focus on the readers’ training, having in view the need to think of activities that encourage the reading in the school space. Thus, we seek to elucidate through a questioning, the importance of literature in the classroom, also highlighting the contributions of the project in the theoretical and practical intrinsic relationship at the university and at the school as fruitful spaces of knowledge and learning. It has as theoretical object the educational literature of Antonio Candido's approach "The right to literature" and Rildo Cosson "literary literacy: theory and practice." The object of analysis is a questionnaire with high school students answers clippings, which seeks to elucidate through what were answered by students, questions concerning to the knowledge they have about literature and in fact the program that starts from the project of insertion of the reading in the classroom accomplished its role in the development of this work. For this reason, we turn to the specialized literature that deals with the theme in question and we adopted the theoretical proposal of some authors, such as: MELO (2011); SAVIANI (2007); TODOROV (2009); PCNs (1998); CANDIDO (2011); COSSON (2009), DIAS (2011); LAJOLO (2005-2010). We hope the research can overcome the foundations of the university and it can contribute to future research in the area of teaching and as follow-up to improvements in education and in teacher training